2023
DOI: 10.1039/d3ta01931d
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid water electrolysis with integrated and cascading reactions using two-dimensional electrocatalysts

Abstract: Electrocatalytic water splitting has become a promising channel for green hydrogen production. However, the high energy barrier and sluggish kinetics of anodic oxygen evolution reaction (OER) burden the industrial application,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 231 publications
0
12
0
Order By: Relevance
“…87−89 It is of great interest to develop alternative energy-saving technologies for hydrogen production, such as using 2D electrocatalysts via hybrid water electrolysis or employing liquid metals via the Al−H 2 O reaction. 90,91 Gabased liquid metal alloys can remarkably enhance the reactivity of Al in the Al−H 2 O reaction by decreasing the Al reactant size, amplifying the reactive surface area, inhibiting the formation of aluminum oxides, and mitigating the surface energy. The highest rate of hydrogen evolution depends upon the composition of the liquid metal alloy.…”
Section: Liquid Metals In Catalysis Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…87−89 It is of great interest to develop alternative energy-saving technologies for hydrogen production, such as using 2D electrocatalysts via hybrid water electrolysis or employing liquid metals via the Al−H 2 O reaction. 90,91 Gabased liquid metal alloys can remarkably enhance the reactivity of Al in the Al−H 2 O reaction by decreasing the Al reactant size, amplifying the reactive surface area, inhibiting the formation of aluminum oxides, and mitigating the surface energy. The highest rate of hydrogen evolution depends upon the composition of the liquid metal alloy.…”
Section: Liquid Metals In Catalysis Applicationsmentioning
confidence: 99%
“…Another study by Kawasaki et al demonstrated the conversion of ethanol to graphitic carbon at the interface of eutectic gallium indium under ultrasonic conditions . In addition, a group of Ga-based catalysts, including compositions, such as Ga, Ga–Sn/In/Zn, and Galinstan, have been developed to facilitate the reaction between aluminum (Al) and water, offering an alternative route for hydrogen production through water splitting. It is of great interest to develop alternative energy-saving technologies for hydrogen production, such as using 2D electrocatalysts via hybrid water electrolysis or employing liquid metals via the Al–H 2 O reaction. , Ga-based liquid metal alloys can remarkably enhance the reactivity of Al in the Al–H 2 O reaction by decreasing the Al reactant size, amplifying the reactive surface area, inhibiting the formation of aluminum oxides, and mitigating the surface energy. The highest rate of hydrogen evolution depends upon the composition of the liquid metal alloy.…”
Section: Liquid Metals In Catalysis Applicationsmentioning
confidence: 99%
“…After years of development, many transition metal electrocatalysts, such as transition metal oxides, hydroxides, sulfides, carbides, sulfides and MOFs, etc., have made significant progress. [6][7][8][9][10][11][12][13] However, these catalysts still generally have poor conductivity, and unsatisfactory catalytic activity and stability. 14 Additionally, most current electrocatalysts are single functional, while bifunctional water electrolysis catalysts are relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…, have made significant progress. 6–13 However, these catalysts still generally have poor conductivity, and unsatisfactory catalytic activity and stability. 14 Additionally, most current electrocatalysts are single functional, while bifunctional water electrolysis catalysts are relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal dichalcogenide (TMD)-based two-dimensional (2D) materials have been strongly in focus recently due to their various structure-driven electronic and optical properties, suitable for a wide range of applications, such as in nanoelectronics, 1,2 spintronics, 3 gas sensing, 4,5 photocatalysis, 1,6–9 electro-catalysis, 10–15 electrochemical energy storage, 16–19 and photonics. 20,21 The hexagonal phase is the most common stable phase of 2D materials.…”
Section: Introductionmentioning
confidence: 99%